AMBULATORY BLOOD PRESSURE VARIABILITY- THE HIGHER THE WORST?. (June 2018) - Magdás, A.; Varga, A.; Podoleanu, C.; Tusa, A.; Incze, A.; Csiki, G.
Abstract : Objective: Our goal was to establish a normal range for blood pressure variability (BPV) defined by average real variability (ARV) and to assess whether it can be considered as an additional cardiovascular risk factor. Design and method: In contrast to one of our previously published study, which included 110 patients, we selected 80 inefficiently treated hypertensive patient, admitted to County Clinical Hospital Turgu Mures, Romania to adjust hypertensive treatment. The definition of hypertension was based on 24-hour ambulatory BP monitoring (ABPM), by using a validate device (ABPM 05, Meditech Ltd, Hungary®), defined as mean 24-hour BP > 130 and/or > 80 mmHg. After calculating BP variability defined as average real variability (ARV), the median value was used to divide the study population in low (LV) or high variability (HV) group. We compared ABPM derived BP parameters, assessed if there is any correlation between pressure overload and variability. Results: In both groups awake systolic BP was nearly equal 143.7 ± 10.5 mmHg, versus 142.4 ± 12.2 mmHg, p = 0.89. Nighttime diastolic BP was significantly higher in the in the LV group 74.09 ± 8.33 versus 69.02 ± 10.22 mmHg, p = 0.017. In the LV group pressure overload expressed as percent time elevation (PTE%) of systolic and diastolic values were 75.2 ± 15.6/45.21 ± 29 % vs. 67.51 ± 18.21/36.13 ± 25.61% in the HV group, p < 0.0001. The systolic BP load was 322.2 ± 195.7 mmHgxh vs. 314.6 ± 183.7 mmHgxh in the HV group, p < 0.0001. The diastolic BP load was 126.2 ± 112.9 mmHgxh vs. 93.02 ± 101.9 mmHgxh in the HV group, p < 0.0001. No correlation was found between BP variability and systolic PTE or BP load in any of the groups, p > 0.05. Conclusions: We found that patients with low variability presented higher BP values and greater pressure overload. High variability is not necessary a dangerous phenomenon if it is accompanied by low BP values without pressure overload. To appreciate the real efficacy of the antihypertensive treatment, a comprehensive assessment of BP values, variability and pressure overload parameters should be included.